The effect of "pumping" and "nonpumping" techniques on velocity production and muscle activity during field-based BMX cycling - Rylands, L. P.; Hurst, H. T.; Roberts, S. J.; Graydon, R. W. (The Journal of Strength and Conditioning Research, 2017)
The aim of the current study was to determine if a technique called "pumping" had a significant effect on velocity production in Bicycle Motocross (BMX) cycling. Ten National standard male BMX riders fitted with surface electromyography (sEMG) sensors completed a timed lap of an indoor BMX track using the technique of pumping, and a lap without pumping. The lap times were recorded for both trials and their surface sEMG was recorded to ascertain any variation in muscle activation of the biceps brachii, triceps brachii, vastus lateralis, and medial gastrocnemius. The findings revealed no significant differences between any of muscle groups (p > 0.05). However, significant differences (p < 0.001) were observed between the pumping and nonpumping trials for both mean lap velocity (42 ± 1.8 km/h, 33 ± 2.9 km/h, respectively) and lap times (43.3 ± 3.1 seconds, 34.7 ± 1.49 seconds, respectively). The lap times recorded for the pumping trials were 19.50 ± 4.25% lower than the nonpumping, whereas velocity production was 21.81 ± 5.31% greater in the pumping trial compared with the nonpumping trial. The technique of pumping contributed significantly to velocity production, although not at the cost of additional muscle activity. From a physiological and technical perspective, coaches and riders should prioritize this technique when devising training regimes.